Nadran As A form Of Cultural Preservation and Local Wisdom Among the Coastal Communities Of Muara Angka In The Face Of Modernization - Paisah Paisah; Arghitta Aricindy; Indriana Eko Armaidi (Sabda: Jurnal Kajian Kebudayaan, 2026)
The Nadran tradition is a longstanding cultural ritual integral to the life of fishing communities along the northern coast of Java Island, particularly in Muara Angke, North Jakarta. This ritual serves as an expression of gratitude for abundant marine resources and a plea for safety for fishermen in their maritime activities. Nadran embodies not only spiritual values but also local wisdom that promotes marine environmental conservation, social solidarity, and mutual cooperation within the fishing community. Despite facing challenges from modernization, urbanization, and social changes, this tradition continues to be maintained through various preservation efforts, including youth involvement, government support, and integration into cultural education and tourism. This study aims to explore the role of Nadran culture as a reflection of local wisdom and its preservation strategies in the modern era.